Synthesis and characterization of a novel pH-responsive drug-releasing nanocomposite hydrogel for skin cancer therapy and wound healing. Issue 46 (10th November 2021) - Gonsalves, Andrea; Tambe, Pranjali; Le, Duong; Thakore, Dheeraj; Wadajkar, Aniket S.; Yang, Jian; Nguyen, Kytai T.; Menon, Jyothi U.
Abstract : Inadequate excision of skin cancer can lead to local recurrence. A novel in situ -forming nanocomposite hydrogel with antimicrobial properties is reported for wound healing and localized pH-responsive treatment against skin cancer recurrence. Abstract : Local skin cancer recurrence occurs in ∼12% of the patients post-surgery due to persistent growth of residual cancer cells. Wound infection is another significant complication following surgery. We report a novel in situ -forming nanocomposite hydrogel (NCH) containing PLGA-carboxymethyl chitosan nanoparticles (186 nm) for localized pH-responsive skin cancer therapy and wound healing. This injectable hydrogel, comprising of a citric acid-derived polymer backbone, gelled within 5 minutes, and demonstrated excellent swelling (283% of dry weight) and compressive strengths (∼5.34 MPa). Nanoparticle incorporation did not significantly affect hydrogel properties. The NCH effluents were cytocompatible with human dermal fibroblasts at 500 μg ml −1 concentration and demonstrated pH-dependent drug release and promising therapeutic efficacy against A431 and G361 skin cancer cells in vitro . Significant zones of inhibition were observed in S. aureus and E. coli cultures on NCH treatment, confirming its antibacterial properties. Our studies show that the pH-responsive NCH can be potentially used for adjuvant skin cancer treatment and wound healing.